Self-harm and Mental Health Characteristics of Prisoners with elevated rates of autistic traits. (July 2021) - Chaplin, Eddie; McCarthy, Jane; Allely, Clare S.; Forrester, Andrew; Underwood, Lisa; Hayward, Hannah; Sabet, Jess; Young, Susan; Mills, Richard; Asherson, Philip; Murphy, Declan
Highlights: Prisoners with elevated autistic traits were significantly more likely to report thoughts about self-harm or suicide than neurotypical prisoners. Prisoners with elevated levels of autistic traits were more likely to report attempting suicide during their life than neurotypical prisoners. Prisoners with elevated levels of autistic traits had higher rates of depressive and anxiety disorders compared to neurotypical prisoners. More research is required to develop effective support and protective systems for prisoners with elevated levels of autistic traits. Abstract: Background: Prevalence studies among prisoners have found rates of 1–4% for autism spectrum disorder (ASD) or autistic traits. However, little is known about those prisoners with high levels of autistic traits. Aim: This aim of this study was to compare the mental health characteristics of prisoners with autistic traits with neurotypical prisoners not screening positive for neurodevelopmental disorders. Method: The study recruited 240 male prisoners from a London prison and screened for autism spectrum disorder using the Autism Quotient (AQ) 20 and 10, and Autism Diagnostic Observation Schedule (ADOS). The Mini International Neuropsychiatric Interview was used to assess for depression, anxiety, self-harm behavior and suicide. Results: Screening using the AQ identified 46 prisoners with significant autistic traits, with 12 meeting the diagnostic threshold for ASD using the ADOS. Those screening positive with autistic traits were significantly more likely to have thought about self-harm and suicide in the past month than neurotypical prisoners and have a comorbid mental disorder. They were also significantly more likely to report having attempted suicide during their lifetime compared to neurotypical peers at a rate of 64.9 % compared to 11.6 % for the neurotypical prisoners. Conclusion: Prisoners with elevated levels of autistic traits were more likely to report self-harm, suicidal thoughts and were more vulnerable to a range of mental disorders than neurotypical prisoners. There is a need for more evidence on the experience of autistic prisoners to inform how pathways should work to improve health outcomes through increased awareness and access to screening and subsequent diagnosis which currently prisons are currently not set up for.